2010
DOI: 10.1080/11250000802658058
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of coarse grain data on forest management to improve bird abundance models

Abstract: We tested the use of coarse grain data on forest management systems to improve habitat suitability models in predicting distribution and abundance of five bird species, nesting in broadleaf forests in Lombardy (Italy). They were the long-tailed tit Aegithalos caudatus, marsh tit Poecile palustris, blue tit Cyanistes caeruleus, wood nuthatch Sitta europaea and short-toed tree-creeper Certhia brachydactyla. Bird data were collected from 4552 point counts from 1992 to 2002. To model the habitat suitability for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…PAs seemed effective in protecting woodland and SDM species because their occurrence indices were larger in PAs than in NPAs. This may be because 30.3% of PAs is woodlands, six out of 22 SDM species are woodland species, and forest areas of Lombardy have increased in extent and have been less intensively exploited in the last two decades (Massimino et al 2010). PAs of Lombardy seem less effective in protecting farmland birds and LDMs.…”
Section: Conclusion and Conservation Implicationsmentioning
confidence: 99%
“…PAs seemed effective in protecting woodland and SDM species because their occurrence indices were larger in PAs than in NPAs. This may be because 30.3% of PAs is woodlands, six out of 22 SDM species are woodland species, and forest areas of Lombardy have increased in extent and have been less intensively exploited in the last two decades (Massimino et al 2010). PAs of Lombardy seem less effective in protecting farmland birds and LDMs.…”
Section: Conclusion and Conservation Implicationsmentioning
confidence: 99%
“…In addition, we include the spatial coordinates of patch centroids (East and North) within each model, to control for two ecological processes that could affect bird species richness in Lombardy. The first process considers differences in bird species assemblages in Lombardy moving from continuous forests of the Alps to fragmented forests of the lowland (i.e., North to the South), while the second process considers a natural increase of forest bird species richness moving from East to West, as observed in other studies carried out in Lombardy (e.g., [30]). All of the continuous independent variables are standardized by subtracting the mean of variables and dividing by the standard deviation (i.e., by centering and scaling).…”
Section: Discussionmentioning
confidence: 72%
“…These results suggest a primary influence of habitat fragmentation in the population dynamics which lead to Short-toed Treecreeper occurrence, even in a Mediterranean landscape. Indeed, habitat fragmentation has been shown to be one of the main threats for the species in forest landscapes (Nour et al, 1999;Bani et al, 2006;Massimino et al, 2010). Specifically, the results showed that occurrence of the species reached a probability equal to or greater than 0.80, when the percent cover of olive groves and orchards within 750 m around the species territory was greater than 85.4% and 37.3% respectively.…”
Section: Figurementioning
confidence: 96%
“…It is considered a Least Concern species (BirdLife International, 2015), even though the subspecies dorotheae (localised on Cyprus) is listed in Annex I of the EU Bird Directive (2009/147/EC). It is considered a typical woodland species (especially broad-leaved or mixed) (Cramp and Perrins, 1993;Bani et al, 2006;Massimino et al, 2010), mainly inhabiting forests made up of trees with rugged bark, because of its bark-gleaning habits (Moreno, 1981;Carrascal and Tellería, 1989;Nour et al, 1997;Almeida and Granadeiro, 2000;Böhm and Kalko, 2009). Nevertheless, it also inhabits parks, orchards, and copses (Cramp and Perrins, 1993;Hagemeijer and Blair, 1997).…”
Section: Introductionmentioning
confidence: 99%